The Role of Employee Engagement in Improving Performance in PT. Bukit Karomah Jaya Panjalu Ciamis - Setiawan, Wahdan Budi; Agenta, Melsa (PT FORMOSA CENDEKIA GLOBAL, 2024)
The influence of employee engagement on employee performance at PT. Bukit Karomah Jaya Panjalu Ciamis is the subject of this research. This research is descriptive quantitative research with a sample of 47 people. Saturated sampling or census is used for sampling. Instrument test, normality test, simple regression analysis, correlation coefficient test, and coefficient of determination test are the analytical tools used. Researchers also tested the hypothesis with the t test. The results of the hypothesis testing analysis show that employee involvement influences PT performance. Karomah Jaya Hill Panjalu Ciamis. The coefficient of determination (R2), found through calculations, is 0.374. This suggests that employee performance is influenced by their engagement, as well as other variables not mentioned here that influence others